Comment on: ApoE-directed therapeutics rapidly clear β-amyloid and reverse deficits in AD mouse models - Fitz, Nicholas F. (2013)
Cramer et al. (Reports, 23 March 2012: 1503-1506) (1) demonstrated that treatment of APP/PS1ΔE9 mice with bexarotene decreased Aβ pathology and ameliorated memory deficits. We confirm the reversal of memory deficits in APP/PS1ΔE9 mice expressing human APOE3 or APOE4 to the levels of their non-transgenic controls and the significant decrease interstitial fluid Aβ, but not the effects on amyloid deposition.